2022
DOI: 10.3389/fphar.2022.821133
|View full text |Cite
|
Sign up to set email alerts
|

Human N-Acetyltransferase 1 and 2 Differ in Affinity Towards Acetyl-Coenzyme A Cofactor and N-Hydroxy-Arylamine Carcinogens

Abstract: Arylamine N-acetyltransferases catalyze the transfer of acetyl groups from the endogenous cofactor acetyl coenzyme A (AcCoA) to arylamine (N-acetylation) and N-hydroxy-arylamine (O-acetylation) acceptors. Humans express two arylamine N-acetyltransferase isozymes (NAT1 and NAT2) which catalyze both N- and O-acetylation but differ in genetic regulation, substrate selectivity, and expression in human tissues. We investigated recombinant human NAT1 and NAT2 expressed in an Escherichia coli JM105 and Schizosaccharo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…Arylamine N-acetyltransferase comprises N-acetyltransferase 1 (NAT1) and N-acetyltransferase 2 (NAT2) in humans (Hein et al, 2022). NAT2 is mainly expressed in the liver and the GI tract (Husain et al, 2007), and is responsible for the N-acetylation polymorphism observed in human populations (Weber and Hein, 1985;McDonagh et al, 2014;Agundez and Garcia-Martin, 2018;Mitchell, 2020).…”
Section: N-acetyltransferase Acetylation Polymorphisms and Tb Treatme...mentioning
confidence: 99%
“…Arylamine N-acetyltransferase comprises N-acetyltransferase 1 (NAT1) and N-acetyltransferase 2 (NAT2) in humans (Hein et al, 2022). NAT2 is mainly expressed in the liver and the GI tract (Husain et al, 2007), and is responsible for the N-acetylation polymorphism observed in human populations (Weber and Hein, 1985;McDonagh et al, 2014;Agundez and Garcia-Martin, 2018;Mitchell, 2020).…”
Section: N-acetyltransferase Acetylation Polymorphisms and Tb Treatme...mentioning
confidence: 99%
“…Recently, Hein et al reported a difference in the affinity of acetyl-CoA for NAT1 and NAT2 (Hein et al, 2022). Using various substrates, they quantified the apparent acetyl-CoA Km for both enzymes and then inferred differences in binding affinity.…”
Section: F the Interaction Of The Nats With Acetyl-coamentioning
confidence: 99%
“…The relationship between Km and binding affinity for a double displacement reaction is complex as the Km is dependent on the off-rate of the acetylated substrate (Minchin and Butcher, 2015;Wang et al, 2005). In the study by Hein et al, the off-rates, at least for two substrates (N-hydroxy-aminofluorene and Nhydroxy-animobiphenyl), were much slower for NAT1 than for NAT2 (Hein et al, 2022). However, this does not explain the differences in acetyl-CoA apparent Km, supporting the conclusion that it has a higher affinity for NAT1 than NAT2.…”
Section: F the Interaction Of The Nats With Acetyl-coamentioning
confidence: 99%
“…DNA adducts not repaired can result in mutations leading to cancer ( Wang et al, 2019 ; NTP, 2021 ). NAT1 catalyzes ABP N-acetyltransferase and N-OH-ABP O-acetyltransferase activities ( Hein et al, 1993 ; Millner et al, 2012 ; Zhou et al, 2013 ; Leggett et al, 2021 ; Leggett et al, 2022 ; Hein et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…NAT1 is selective for acetylation of 4-alkylanilines due to binding to V216, which is replaced by S216 in NAT2 ( Liu et al, 2007 ). NAT1 exhibits higher affinity than NAT2 for the O-acetylation of N-hydroxy-arylamine carcinogens such as N-OH-ABP ( Hein et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%